2012
DOI: 10.3746/jkfn.2012.41.4.519
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Compounds and Antioxidant Activities of Sweet Potatoes with Cultivated Conditions

Abstract: Effects of cultivated conditions on antioxidant compounds and antioxidant activities of sweet potatoes (Ipomoea batatas (L.) Lam) were determined. The cultivated variety was Shinyulmi, and they were cultivated in a conventional culture, successful cropped hairy vetch culture, successful cropped barley cultivation, successful cropped rye cultivation, successful cropped mix-seeding of hairy vetch and barley, successful cropped mix-seeding of hairy vetch and rye, and not fertilizer. The brix degree, moisture, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 18 publications
2
1
0
2
Order By: Relevance
“…According to a study by Li et al ( 2012 ), the ABTS radical scavenging activity of sweet potato leaves and stalks was in the range of 8.02–14.95 AAE/g, and the content of the leaves was higher than that of the stalks. In addition, according to a study by Woo et al ( 2012 ), the ABTS and DPPH radical scavenging activity of sweet potato tubers were 4.38–6.63 and 5.46–9.58 mg/g, respectively, and are similar to the results of this study.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…According to a study by Li et al ( 2012 ), the ABTS radical scavenging activity of sweet potato leaves and stalks was in the range of 8.02–14.95 AAE/g, and the content of the leaves was higher than that of the stalks. In addition, according to a study by Woo et al ( 2012 ), the ABTS and DPPH radical scavenging activity of sweet potato tubers were 4.38–6.63 and 5.46–9.58 mg/g, respectively, and are similar to the results of this study.…”
Section: Resultssupporting
confidence: 92%
“…According to a study by Lee, Park, et al (2007), the high phenolic substances in sweet potato parts and their antioxidant activity corroborate the high content of phenolic substances and good antioxidant activity Inhibitory activity( % ) = (1 − absorbance at the sample addition ∕ absorbance at no addition) × 100 et al (2012), the ABTS radical scavenging activity of sweet potato leaves and stalks was in the range of 8.02-14.95 AAE/g, and the content of the leaves was higher than that of the stalks. In addition, according to a study by Woo et al (2012), the ABTS and DPPH radical scavenging activity of sweet potato tubers were 4.38-6.63 and 5.46-9.58 mg/g, respectively, and are similar to the results of this study.…”
Section: Abts and Dpph Radical Scavenging Activitysupporting
confidence: 89%
“…In this study, ESB showed an excellent inhibit lipid peroxidation ( Figure 2C). The phenolic compounds contained in natural plants were reported to be associated with radical scavenging activity [26]. Also, Maresca et al [27] reported that removal of ROS with antioxidants is effective in inhibiting melanin biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…웰빙 건강식품으로 알려진 고구마에 관한 연구로 는 고구마의 품종별 성분연구 (Kim 1996), 고구마를 이용한 식사대용 유동식 제품개발 (Hong et al 1999), 고구마의 어원과 품성에 대한 문헌연구 (Kim 2011), 고구마의 육질색 종류별 고구마 분말의 이화학적 특 성 , 재배조건에 따른 고구마의 항산 화성분 연구 (Woo et al 2012), 고구마 네가지 품종 의 조리방법에 따른 생리활성 변화 등의 연구가 보고되고 있다. 그 밖에도 항산화 및 생 리활성 Kim et al 2015;Park et al 2015), 항알레르기 (Kwak et al 2013) 및 항돌연변이 Park et al 2011 than that in PSP.…”
unclassified